Analysis of the failure mechanism of multi-beam steel–concrete composite bridge under car explosion. Issue 3 (February 2020) - Zhu, Zhao; Li, Yuan; He, Shuanhai; Ma, Chao
The objective of this study is to investigate the damage mechanism of a multi-beam steel–concrete composite bridge under car explosion. The steel–concrete composite bridge is widely used in expressways and urban viaducts. Explosives are distributed in multiple locations above the deck to avoid stress concentration. The explosion damage analysis is carried out with the equivalent trinitrotoluene of 50 kg, which represents a car explosion in the state of full oil tank. The multi-Euler domain method based on the fully coupled Lagrange and Euler models is adopted for the structural analysis of the explosion process with the commercial software Autodyn. This study shows that the structural failure goes through three stages: elastoplastic, plastic, and plastic hinge with full section. From 1/8 to 1/2 of the bridge span, the failure times of the bridge are 277, 164, 133, and 133 ms, matching the displacements of 412, 889, 819, and 819 mm, respectively, while the explosion occurs above steel beams. For the explosion occurring above the concrete deck, the failure times are 335, 154, 121, and 125 ms, corresponding to the deflections of 479, 930, 722, and 752 mm. When the explosion occurs from bearings to the quarter of the bridge span, shear failure of steel beams occurs before bending failure, and both of them control the explosion-resistant design of structures. For the detonation occurring at 1/4 to 1/2 of the bridge length, the explosion damage of the steel–concrete composite bridge is controlled by flexural failure, and only local shear failure occurs. The multi-beam steel–concrete composite bridge which meets the design requirements will generate plastic hinge and lose bearing capacity under car explosion wherever the explosion occurs.